Win/win partnerships between Geneva health-related institutions and caregivers of people with dementia: a descriptive cross-sectional study - Marie-Conception Leocadie; Hélène Lefebvre; Monique Rothan-Tondeur (BMC, 2019)
Abstract Background In the context of an ageing population and an increase in the appearance of chronic diseases, the commitment of caregivers makes it possible for people confronted with disease to remain at home. Over time, they need support to overcome their difficulties. They also show a need for recognition for their participation in the economic maintenance of the health system. To promote this support, so-called "win/win" partnerships are envisaged. Research is needed to identify the building blocks of an innovative intervention. Methods A cross-sectional descriptive study was carried out with health institutions in the canton of Geneva to identify the proportion of institutions with a positive opinion on partnership with caregivers. It has also identified potential partnerships with caregivers of people facing dementia and possible compensation in exchange for the provision of their skills. Descriptive statistics are presented according to their frequencies and relative percentages (categorical variables), as well as by their mean, standard deviation and median (continuous variables). Logistic regression models were used to assess the factors associated with a favorable opinion towards win/win partnerships. Results The proportion of executives of health-related institutions with a positive opinion of partnership with caregivers is high: 74.7% (95% CI: 64.8-83.1%). Several types of potential partnerships have been identified between health institutions and caregivers. Areas in which certain activities have been identified as being able to be carried out by caregivers include governance, care, provision of services, accompaniment and support, training and research. Types of compensation for caregivers have also been highlighted. Conclusion This study shows that some areas activities of health facilities in the canton of Geneva could be the subject of win-win partnerships with caregivers of people with dementia. Positive view of health executives on partnership with caregivers is encouraging. In the future, innovative projects can emerge to meet the needs of each party.